Ethics in light of childhood - Wall, John, 1965- (Georgetown University Press, 2010)
Childhood faces humanity with its own deepest and most perplexing questions. An ethics that truly includes the world's childhoods would transcend pre-modern traditional communities and modern rational autonomy with a postmodern aim of growing responsib.